Femtosecond laser micromachining photonic and microfluidic devices in transparent materials - Osellame, Roberto. (Topics in applied physics, 2012)
Femtosecond laser micromachining of transparent material is a powerful and versatile technology. In fact, it can be applied to several materials. It is a maskless technology that allows rapid device prototyping, has intrinsic three-dimensional capabilities and can produce both photonic and microfluidic devices. For these reasons it is ideally suited for the fabrication of complex microsystems with unprecedented functionalities. The book is mainly focused on micromachining of transparent materials which, due to the nonlinear absorption mechanism of ultrashort pulses, allows unique three-dimensional capabilities and can be exploited for the fabrication of complex microsystems with unprecedented functionalities.This book presents an overview of the state of the art of this rapidly emerging topic with contributions from leading experts in the field, ranging from principles of nonlinear material modification to fabrication techniques and applications to photonics and optofluidics.